2012
DOI: 10.1080/10934529.2012.645786
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of long-chainn-alkanes in soil microcosms by two actinobacteria

Abstract: The ability of two recently isolated actinobacteria, that degrade medium and long chain n-alkanes in laboratory water medium, was investigated in soil microcosms using different standard soils that were artificially contaminated with n-alkanes of different length (C(12)- C(20)- C(24)- C(30)). The two strains, identified as Nocardia sp. SoB and Gordonia sp. SoCp, revealed a similar high HC degradation efficiency with an average of 75% alkane degraded after 28 days incubation. A selectivity of bacteria towards n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…; De Pasquale et al . ). The presence of Alcanivorax and Marinobacter in natural environments or enrichment by laboratory is generally combined with the presence of other bacterial strains (Santisi et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; De Pasquale et al . ). The presence of Alcanivorax and Marinobacter in natural environments or enrichment by laboratory is generally combined with the presence of other bacterial strains (Santisi et al .…”
Section: Discussionmentioning
confidence: 97%
“…Hydrocarbonoclastic bacteria such as Alcanivorax and Marinobacter are well known for their ability to degrade hydrocarbons alone with a high rate (Cappello et al 2016) but a single species can metabolize only a limited range of hydrocarbon substrates because it does not have all the enzymatic machinery to degrade a pollutant until its complete mineralization (Mahjoubi et al 2013). For this reason, a consortium of many different bacterial species, with broad enzymatic capacities, is usually involved in oil degradation (R€ oling et al 2002;De Pasquale et al 2012). The presence of Alcanivorax and Marinobacter in natural environments or enrichment by laboratory is generally combined with the presence of other bacterial strains (Santisi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…By the advancement in the biotechnology it is possible to enhance the degradation of crude oil contaminants. Genetic engineering can be used to construct such bacterial strains that contain Lin-A and RHD genes translating hydroxylating dioxygenase enzymes that are used to degrade polycyclic hydrocarbons [66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Future Prospectsmentioning
confidence: 99%
“…Bacterial degradation of n-alkanes is common in aerobic environments and has been identified in a variety of natural environmental settings (Whyte et al, 2002;Quatrini et al, 2008;Shibata and Robert, 2009;Kuhn et al, 2009;Powell et al, 2010;Panicker et al, 2010;Jurelevicius et al, 2012;De Pasquale et al, 2012;Hassanshahian et al, 2013Hassanshahian et al, , 2014Bayat et al, 2015). Dellagnezze et al (2014) found that up to 99% of n-alkanes ranging in length from n-C 14n-C 33 were degraded by bacteria under controlled conditions in as short as 21 days (Dellagnezze et al, 2014).…”
Section: Introductionmentioning
confidence: 99%